DEVELOPMENT OF STUDENT SHEET ACTIVITIES USING THE OPEN-ENDED APPROACHES FOR CLASS VII SMP / MTs ON QUADRANGLE TWO-DIMENSIONAL SHAPES MATERIAL - Rika Fajar Rahmadi; Sumargiyani Sumargiyani (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
Learning is a human process to achieve a wide range of competencies, skills, and attitudes. The availability of mathematics teaching materials at SMP Negeri 1 Tempel and MTs Negeri 2 Sleman still lacks, especially the teaching materials that use The Open-Ended approach. The student worksheet based on The Open-Ended approach is one of the teaching materials alternatives that can be used to facilitate teachers and empower students. This research aims to develop and test the feasibility of the student worksheet using The Open-Ended approach for grade VII SMP / MTs students in the second semester on the Quadrangle two-dimensional shapes material. Â The research was done through a procedural development model. The stages in developing student worksheets using The Open-Ended approach were preliminary research, data collection, product development, product validation, and product trial. The subjects of research and development were materials experts, media experts, and students. In this research, material experts and media experts were expert lecturers and grade VII junior high school mathematics teachers. Data collection techniques used were interviews and questionnaires. The type of data used was qualitative data, which was then converted into quantitative data. Data analysis using a qualitative descriptive analysis technique was used to describe the development of student worksheets. The descriptive statistic was to analyze the questionnaire of the feasibility test of material experts, media experts, and the student response to the worksheet. The result of the research and development succeeded in making student worksheets using The Open-Ended approach for grade VII SMP / MTs student on the Quadrangle materials. The assessment of the material experts, media experts, and student responses to the student worksheet using The Open-Ended approach is 84.21% with very reasonable criteria. These results indicate that the student worksheet using The Open-Ended approach for grade VII SMP / MTs student on the Quadrangle two-dimensional shapes material is very feasible in the learning process